Systematic physical training in schools - Lyman, Laura Lillian (My University, 1906)
Introduction: It is not until recent years that Physical Training, as one phase of a child's development, has been given any consideration. The fact that a growing child needs exercise and recreation has been constantly overlooked, and the introduction of such systems into our schools is still comparatively new. Many persons, highly educated intellectually, argue strongly against the need of Physical Training in the schools of today. They maintain that the child has sufficient exercise during recesses and the noon intermission to not necessitate the taking of valuable time in the school-room for regular gymnastic exercises. Others, however, who have given this subject careful study, agree that when a thoroughly systematized form of Physical Training is given in conjunction with the mental development, that a marked betterment of intellectual powers is the result. Physical Training is, by no means intended merely to restore imperfect health, it is an institution intended to benefit both mind and body, and is a means of education and training, fully as important as any other branch. By developing the body to its highest degree of healthfulness, the brain-power is undoubtedly increased and strengthened, and the result is an increased power for learning in all branches.
Citation: Lyman, Laura Lillian. Systematic physical training in schools. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Education; Physical Education; Theses